Urban Architectural Characteristics as a Reflection of Local Identity in Urban Areas - Puspita utari; Nurhayati Kamaruddin (Universitas Ichsan Sidenreng Rappang, 2025)
Urban architecture not only serves as a space for human activities but also represents the local identity that grows and develops over time. This research aims to identify and analyze the characteristics of urban architecture that reflect local values in Tanete Riaja District. Using a qualitative descriptive approach, data was collected through field observations, visual documentation, and interviews with community leaders and relevant parties. The results show that architectural elements such as building forms, local materials, spatial layouts, and cultural symbols are closely connected to the history, traditions, and social life of the local community. The local identity in the urban architecture of Tanete Riaja is reflected in the continuity of cultural values that are preserved despite the process of modernization. This study is expected to contribute to the preservation of local identity in urban planning and development in the future.